Methyl jasmonate modulation reduces photosynthesis and induces synthesis of phenolic compounds in sweet potatoes subjected to drought - Pereira Yoshida, Camila Hatsu; Pacheco, Ana Claudia; Lapaz, Allan de Marcos [UNESP]; Gorni, Pedro Henrique; Vitolo, Hilton Fabricio; Bertoli, Suzana Chiari (Inst Agronomico, 2020)
Sweet potato [Ipomoea batatas (L.) Lam.] has wide adaptability to different climatic conditions. However, its yield can be affected by prolonged periods of drought. Application of exogenous jasmonates can modulate several physiological and biochemical processes, improving plant tolerance to abiotic stress. This study sought to evaluate the role of exogenous application of methyl jasmonate (MeJA) in attenuating the adverse effects of drought stress by physiobiochemical analyses and their impact during the early initiation of tuberous roots. The experimental design was completely randomized and arranged in a 2 x 2 factorial, comprised of two concentrations of a MeJA plant regulator [without (0 mmol.L-1)and with (13 mmol.L-1) application] and two water regimes (optimum and drought conditions, corresponding to a field capacity of 100 and 40%, respectively). Plants treated with MeJA showed a reduction in total leaf area and leaf dry biomass but increased adventitious root dry biomass. In addition, MeJA application in sweet potato plants affected photosynthetic performance and increased and antioxidant phenolic compounds, carotenoids, anthocyanins,and proline. The evaluated response mechanisms showed that the severity of drought was more prominent than the positive effects of MeJA, since the increases on antioxidant pigments and secondary metabolites were not sufficient to mitigate stress caused by drought, which was reflected in the reduced tuberous root production.
Keywords: photosynthetic performance; phenylalanine ammonia lyase; tuberous roots; Ipomoea batatas (L.)